Restricted dog leucocyte antigen (DLA) class II haplotypes and genotypes in Beagles. Issue 3 (March 2015) - Soutter, Francesca; Kennedy, Lorna J.; Ollier, William E.R.; Solano-Gallego, Laia; Catchpole, Brian
Highlights Dog leucocyte antigen (DLA) class II genes were examined in laboratory Beagles. Laboratory Beagles represent a different immunogenetic pool compared with pet Beagles. Beagles do not express the full range of DLA haplotypes seen in the canine population. Beagles could be suitable for vaccine studies if genetic diversity is maintained.